2021
DOI: 10.3389/fnut.2021.701644
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus paracasei S16 Alleviates Lumbar Disc Herniation by Modulating Inflammation Response and Gut Microbiota

Abstract: Lumbar disc herniation (LDH) is a common cause for low back pain. In this study, we aimed to explore the effects of a specific Lactobacillus paracasei (L. paracasei), L. paracasei S16, on the symptoms of LDH using a mouse model of LDH. The results showed that L. paracasei S16 treatment improved the behavior, increased the cell proliferation, and decreased the apoptosis in LDH mice. Moreover, L. paracasei S16 treatment alleviated the aberrant inflammation response in the LDH mice, which is characterized by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
0
15
1
Order By: Relevance
“…Lumbar disc herniation mice receiving L. paracasei , but not sham, exhibited an attenuated behavioral pain response and decreased inflammatory response in the dorsal root ganglia. 112…”
Section: Gut Microbiome and Painmentioning
confidence: 99%
“…Lumbar disc herniation mice receiving L. paracasei , but not sham, exhibited an attenuated behavioral pain response and decreased inflammatory response in the dorsal root ganglia. 112…”
Section: Gut Microbiome and Painmentioning
confidence: 99%
“…For example, L. paracasei has been proved to suppress the in ammatory cytokines secretion (including TNF-α, IL-6, IFNγ), and elevate the antioxidant enzymes activities [including catalase (CAT) and superoxide dismutase (SOD)] [11]. L. paracasei S16 intervention also ameliorated the aberrant in ammation response and reduced the percentage of Th1 and Th2 cells and Th17/Treg ratio [12]. Furthermore, a previous study elaborated that Long-term intervention of L. paracasei remarkably elevated the proportion of bene cial bacteria and remarkably decreased the proportion of harmful bacteria [13].…”
Section: Introductionmentioning
confidence: 99%
“…Rajasekaran et al (2020) found a higher abundance of Oxalobacter in India human degenerated intervertebral disc and Lactobacillus was found to be abundant in normal disc compared to disc herniation, which follows a similar trend to our results. In lumbar disc herniation mouse models, a relatively high abundance of Ruminococcaceae in gut is associated with improved behavior, increased cell proliferation and decreased apoptosis (Wang et al, 2021). Therefore, gut microbiota may affect LBP mediating dysbiosis of microbiota in intervertebral disc.…”
Section: Discussionmentioning
confidence: 99%